2017
DOI: 10.1111/jmwh.12619
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Disorder in Pregnancy

Abstract: Opioid use disorder (OUD) in pregnancy has increased significantly in the past 10 years. Women with OUD may often be undertreated or untreated because of limited accessibility to treatment, particularly in rural areas. Because detoxification is not recommended during pregnancy due to the potential for adverse outcomes in the fetus and a high risk of relapse for the woman, more primary care providers need to be well versed in opioid-assisted therapy. In addition, recent changes in Food and Drug Administration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…We also found that younger patients with gastroparesis were more likely to have OUD, as were females and patients with Medicaid insurance. Our finding in the gastroparesis cohort is consistent with a CDC report that showed a 4-fold increase in OUD during labor and delivery; safety measures have since been introduced to limit the maternal and neonatal complication rate [27,28]. This emphasizes the need for special attention to gastroparesis management for women of childbearing age.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that younger patients with gastroparesis were more likely to have OUD, as were females and patients with Medicaid insurance. Our finding in the gastroparesis cohort is consistent with a CDC report that showed a 4-fold increase in OUD during labor and delivery; safety measures have since been introduced to limit the maternal and neonatal complication rate [27,28]. This emphasizes the need for special attention to gastroparesis management for women of childbearing age.…”
Section: Discussionsupporting
confidence: 89%
“…Both limited economic means and Medicaid coverage may constrain treatment options for rural residents with OUD, who also face workforce and health services shortages for both obstetric care and substance use/mental illness. 40,43 Implications While many resources dedicated to combating maternal OUD and NAS are concentrated in urban teaching hospitals, [6][7][8] we demonstrated increases in OUD and NAS diagnosis in all hospital settings, including more than half of rural residents with maternal OUD who give birth in rural hospitals. Rural hospitals may be less well equipped to handle the complex needs of this patient population.…”
Section: Discussionmentioning
confidence: 83%
“…These women and infants may require specialized and high acuity services, which are frequently limited in rural hospital settings and at hospitals with lower levels of maternal care. [6][7][8]12,14 The findings from this analysis show that clinicians in rural hospitals see substantial numbers of patients impacted by opioid-affected births as well as other clinical complications, warranting efforts to support complex patient needs in all hospital settings.…”
Section: Discussionmentioning
confidence: 92%
“…However, despite current recommendations, the majority of pregnant women with OUD do not receive pharmacotherapy during pregnancy . Roper and Cox summarized prenatal considerations for women with OUD in a review that highlighted the importance of pharmacotherapy treatment programs to avoid the risk of relapse and adverse effects on the fetus . Buprenorphine is generally preferred over methadone given its equivalent safety and efficacy as well as the increased ease by which the medication can be obtained .…”
Section: Introductionmentioning
confidence: 99%